Verdien Homo naledi "n plek in ons familie-album? "n Teologiese besinning oor die evoluering van spiritualiteit met spesifieke verwysing na die begraafplaasteorie van Lee Berger en die " Rising-Star "-ekspedisie - Pienaar, Kobus (HTS teologiese studies, 2017)
The discovery of a new homonin species called Homo naledi evoked unprecedented interest, even outside the scientific disciplines who are researching extinct homonin species. The reason for this is that Prof. Lee Berger, attached to the University of the Witwatersrand and his team, known as the Rising Star-expedition, came to the conclusion that the fossils that were discovered in the Dinaledi cave room in Sterkfontein outside Johannesburg in 2013, were placed there deliberately. The theory postulates the possibility of symbolic or ritual behaviour by a species that lived and later became extinct approximately 1 to 2 million years ago. If this is indeed the case, it also offers theologians the opportunity to join the conversation with regard to the evolvement of our spirituality and religiousness. This article is an attempt to render a contribution, with the data available to us, about the value of the prehistoric signs of spirituality with specific reference to the so-called cemetery theory. Together with this, other usable theories will be employed to consider the possible signs of ritual and symbolic behaviour by Homo naledi. The condition for a meaningful discussion about the evolvement of our spirituality and religiousness is that epistemological contours be clearly drawn. With the first part of the article these contours are drawn and with the second part the possible implications of the cemetery theory are reviewed.